SCE560 : Science teaching methodologies / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course enables students to appreciate and put into practice the various theories relevant to the teaching and learning of science as evidenced from recent science education literature. Students are encouraged to translate the theories discussed into their teaching practices wherever and whenever appropriate. KSSM science content is used as a mean of providing a context for acquiring, developing, and practicing the innovative science-classroom instructional skills created. In short, students will be aspired to be an effective science facilitator in the cognitive, the affective, and the practical domains of science.